مقاربة نظرية في تقنية التناص - غرابي, بوبكر; تومي, سعيد (جامعة الوادي - University of Eloued, 2021)
ملخص: لقد كان ظهور مفهوم التناص في الدراسات النقدية الحديثة كرد فعل على المفاهيم النقدية البنيوية التي أكدت انغلاق النص على ذاته بحجة قيامه بنفسه، فجاءت الدراسات التي تنتمي إلى ما بعد البنيوية، ومنها التفكيكية التي عدت النص بنية من الفجوات التي مهدت بدورها إلى ظهور نظرية التلقي في الأدب والفن، ثم ظهر مفهوم التناص الذي يعتبر النص بنية من النصوص الغائبة، إذ إن هذه الدراسات والنظريات أثبتت قصور الدراسات التي اعتبرت انغلاق النص واستغلاقه المزعوم، وفي هذا المجال ظهر مفهوم التناص على يد الباحثة(جوليا كريستيفا) التي طورت هذا المفهوم عن مفهوم الحوارية أو الصوت المتعدد الذي اقترحه الناقد والمفكر الروسي(ميخائيل باختين) . الكلمات المفتاحية: التناص، الحوارية، ما بعد البنيوية، التفكيكية. Abstract: The emergence of the concept of intertextuality in modern critical studies was a reaction to structural monetary concepts that confirmed the closure of the text on itself on the pretext of its own existence, so studies that belong to the post-structuralism, including deconstruction that came back the text with the intention of the gaps that in turn paved the way to the emergence theory in Literature and art, then the concept of intertextuality emerged, which considers the text as a structure of the absent texts, as these studies and theories proved the limitations of studies that considered the text’s alleged closure and closure, and in this field the concept of intertextuality appeared at the hands of researcher (Julia Kristeva) that developed this concept of the concept of dialogue Or Multiple voice proposed by the Russian critic and thinker (Mikhail Bakhtin). Key words: Intertextuality, discourse, post structuralism, deconstruction.
مقال
Keywords: التناص ; الحوارية ; ما بعد البنيوية ; التفكيكية